Polymeric micelles for the ocular delivery of triamcinolone acetonide: preparation and in vivo evaluation in a rabbit ocular inflammatory model. (1st January 2020) - Safwat, Mohamed A.; Mansour, Heba F.; Hussein, Amal K.; Abdelwahab, Soha; Soliman, Ghareb M.
Abstract: The aim of this study was to prepare triamcinolone acetonide (TA)-loaded poly(ethylene glycol)- block -poly(ε-caprolactone) (PEG- b -PCL) and poly(ethylene glycol)- block -poly(lactic acid) (PEG- b -PLA) micelles as a potential treatment of ocular inflammation. The micelles were evaluated for particle size, drug loading capacity and drug release kinetics. Selected micellar formulations were dispersed into chitosan hydrogel and their anti-inflammatory properties were tested in rabbits using a carrageenan-induced ocular inflammatory model. Particle size ranged from 59.44 ± 0.15 to 64.26 ± 0.55 nm for PEG- b -PCL and from 136.10 ± 1.57 to 176.80 ± 2.25 nm for PEG- b -PLA micelles, respectively. The drug loading capacity was in the range of 6–12% and 15–25% for PEG- b -PCL and PEG- b -PLA micelles, respectively and was dependent on the drug/polymer weight ratio. TA aqueous solubility was increased by 5- and 10-fold after loading into PEG- b -PCL and PEG- b -PLA micelles at a polymer concentration as low as 0.5 mg/mL, respectively. PEG- b -PLA micelles suspended in chitosan hydrogel were able to sustain the drug release where only 42.8 ± 1.6% drug was released in one week. TA/PEG- b -PLA micelles suspended in chitosan hydrogel had better anti-inflammatory effects compared with the plain drug hydrogel or the drug micellar solution. Complete disappearance of the corneal inflammatory changes was observed for the micellar hydrogel. These results confirm the potential of PEG- b -PLA micelles suspended in chitosan hydrogel to enhance the anti-inflammatory properties of triamcinolone acetonide.